Natural variations in the promoter of OsSWEET13 and OsSWEET14 expand the range of resistance against Xanthomonas oryzae pv. oryzae - Zaka, Abha; Grande, Genelou; Coronejo, Thea; Quibod, Ian Lorenzo; Chen, Chun-Wei; Chang, Su-Jein; Szurek, Boris; Arif, Muhammad; Vera Cruz, Casiana; Oliva, Ricardo (Public Library of Science, 2018)
Bacterial blight, caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the major diseases that impact rice production in Asia. The bacteria use transcription activator-like effectors (TALEs) to hijack the host transcription machinery and activate key susceptibility (S) genes, specifically members of the SWEET sucrose uniporters through the recognition of effector-binding element (EBEs) in the promoter regions. However, natural variations in the EBEs that alter the binding affinity of TALEs usually prevent sufficient induction of SWEET genes, leading to resistance phenotypes. In this study, we identified candidate resistance alleles by mining a rice diversity panel for mutations in the promoter of OsSWEET13 and OsSWEET14, which are direct targets of three major TALEs PthXo2, PthXo3 and AvrXa7. We found natural variations at the EBE of both genes, which appeared to have emerged independently in at least three rice subspecies. For OsSWEET13, a 2-bp deletion at the 5th and 6th positions of the EBE, and a substitution at the 17th position appear to be sufficient to prevent activation by PthXo2. Similarly, a single nucleotide substitution at position 10 compromised the induction of OsSWEET14 by AvrXa7. These findings might increase our opportunities to reduce pathogen virulence by preventing the induction of SWEET transporters. Pyramiding variants along with other resistance genes may provide durable and broad-spectrum resistance to the disease.